2017
DOI: 10.1038/nsmb.3442
|View full text |Cite
|
Sign up to set email alerts
|

Rps26 directs mRNA-specific translation by recognition of Kozak sequence elements

Abstract: We describe a novel approach to separate two ribosome populations from the same cells and use this method, and RNA-seq, to identify the mRNAs bound to S. cerevisiae ribosomes with and without Rps26, a protein linked to the pathogenesis of Diamond Blackfan Anemia (DBA). These analyses reveal that Rps26 contributes to mRNA-specific translation by recognition of the Kozak sequence in well-translated mRNAs, and that Rps26-deficient ribosomes preferentially translate mRNA from select stress response pathways. Surpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
179
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(192 citation statements)
references
References 68 publications
13
179
0
Order By: Relevance
“…This role could be in addition to the role in promoting the rotated state described herein, and is therefore fully consistent with this report, although alternative explanations for the genetic interaction between Fap7 and Tsr2 have been described (Ferretti et al, 2017). …”
Section: Discussionsupporting
confidence: 92%
“…This role could be in addition to the role in promoting the rotated state described herein, and is therefore fully consistent with this report, although alternative explanations for the genetic interaction between Fap7 and Tsr2 have been described (Ferretti et al, 2017). …”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, RPS26 is involved in the recognition of the Kozak sequence (67). Indeed, ribosomes that lack RPS26 have a greater propensity to translate proteins that do not start with canonical Kozak leader sequences.…”
Section: Dynamic Proteomics Enabled the Profiling Of Cellular Responsmentioning
confidence: 99%
“…Even the prominent example suggesting ribosome specialization, RPL38 regulating HOX genes [39,42], falls short of direct proof since (i) its exclusive specificity to 3 HOX is implied and not directly measured and (ii) the existence of ribosomes lacking RPL38 in wildtype cells is assumed, not measured. However, more recent data from the Barna lab identified distinct mRNA subsets exhibiting enriched or diminished ribosome association with subsets of ribosomes enriched for RPL10a [24], and Ferretti & colleagues demonstrated a specific role for RPS26-containing ribosomes [37]. These data had the advantage that the ribosomes and their mRNA specificity were identified from transgenic cells, rather than knockouts or a disease state.…”
mentioning
confidence: 99%
“…In favor of broader specificity, Zhen Shi and colleagues recently demonstrated this can occur in wild-type cells with ribosomes enriched in RPL10A preferentially translating a subset of mRNAs containing IRES elements [24]. Recent work in yeast also identified RPS26-deficient ribosomes that preferentially bind mRNAs involved in select stress response pathways by selecting mRNAs with deviations in their Kozak sequence at the -4 position [37]. Horos et al, 2012 [38] reported that a single RP, S19, affects the ribosomal density along hundreds of mRNAs essential for the differentiation of murine and human erythroblasts.…”
mentioning
confidence: 99%